2005
DOI: 10.1097/01.ccm.0000163401.77581.86
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous translaryngeal versus surgical tracheostomy: A randomized trial with 1-yr double-blind follow-up*

Abstract: Compared with ST, the main advantages of TLT are that it is more rapid and associated with less postoperative bleeding. Infectious complications, particularly postoperative bacteremia, and long-term effects (physical and emotional) are similar with the two procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
94
1
10

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(105 citation statements)
references
References 27 publications
0
94
1
10
Order By: Relevance
“…We also saw a lower incidence of pneumonia in patients undergoing percutaneous tracheostomy (59 vs. 75%, P = 0.011, OR: 0.49 (CI 95%: 0.27-0.89)), whereas others authors have found no difference in the incidence. 79,80 We did not find any difference in terms of mortality and perioperative complications. According to our When a tracheostomy is performed after anterolateral cervical spine fixation, the two incisions come in very close contact, which poses the potential risk of cross-contamination and, therefore, of much feared infection of the osteosynthetic material.…”
Section: Discussionmentioning
confidence: 72%
“…We also saw a lower incidence of pneumonia in patients undergoing percutaneous tracheostomy (59 vs. 75%, P = 0.011, OR: 0.49 (CI 95%: 0.27-0.89)), whereas others authors have found no difference in the incidence. 79,80 We did not find any difference in terms of mortality and perioperative complications. According to our When a tracheostomy is performed after anterolateral cervical spine fixation, the two incisions come in very close contact, which poses the potential risk of cross-contamination and, therefore, of much feared infection of the osteosynthetic material.…”
Section: Discussionmentioning
confidence: 72%
“…La incertidumbre sobre la seguridad de la TPC en relación a la TQx se ha ido despejando en los últimos años [36][37][38] . Silvester y cols 39 , randomizaron 200 pacientes a TPC con la técnica de Ciaglia o TQx.…”
Section: Discussionunclassified
“…PCT is easy and safe, and can be performed at the bedside in the ICU, avoiding the risks associated with transport of critically ill patients to the operating room [20,21]. Moreover, it is a simple procedure to learn and, in our experience, a minimum of five to ten procedures under the supervision of an expert physician are advisable to achieve adequate training.…”
Section: No Patientsmentioning
confidence: 99%